Letramento imagético na educação infantil : olhar ativo das crianças a partir da leitura de imagens - Araújo, Diana Maria Alves de (2024)
The research proposal for this study envisages starting the development of image literacy, approached through reading images, with children from Kindergarten II, from the Maria Graciete Ramos Castro Municipal Creche, in the municipality of Gurjão-PB. We understand that image literacy is a social and cultural acquisition of image language. In this sense, by strengthening this type of learning we are enhancing the cultural experiences that students already bring from their daily lives. Based on the references indicated in the proposal, we understand that the images are loaded with meanings and, therefore, by encouraging these children to encounter these images, we are ensuring their experience with Art. In this sense, a new challenge would be presented to education: that of recognizing image literacy as a significant element for educational processes. By proposing this type of activities, we establish a creative interaction in the school environment, encouraging children to become increasingly autonomous in the development of language and their speeches, regardless of whether or not they have already acquired reading and spelling skills. Therefore, in the teaching-learning process we believe that children's literature and image language are allies, as this union is a powerful tool to guarantee learning. For this reason, the purpose of this study is to help children in Early Childhood Education – Kindergarten II begin the process of image literacy through experimentation and appreciation of images.